Stereospecificity of pig liver esterase in the hydrolysis of racemic esters derived from 1,8-cineole - Loandos, Maria del Huerto (2006)
The efficient synthesis of biological active compounds, so much natural as not natural, frequently requires chiral syntons. Enzymes as chiral catalysts are widely used for this purpose owing to the fact that it is usually difficult to carry out highly enantioselective transformations using chemical methods. Esterases, such as that of pig liver (PLE), a serine hydrolase, is able to hydrolize a wide range of substrates with high stereoselectivity. This enzyme has been used for the hydrolysis of different esters, mainly meso and prochiral diesters. 1,8-cineole (1) or eucalyptol is a bicyclic monoterpene ether widespread in plant kingdom (Fig. 1). This is the main constituent of a number of essential oils, in particular those produced by several species of the genus Eucaliptus. We selected the racemates of acetates 5a and 6a, and the diacetate 6b with the purpose of studying the specificity of PLE and its utility for preparing pure enantiomers.   Our results indicate that the enzyme is effective for the enantioselective hydrolysis of the racemate of 5a. However, it doesn´t discriminate the racemate of the primary acetate 6a. The results of the hydrolysis of the diacetate 6b analysed after 3 hours incubation gave a 1:1 mixture of the hydroxyacetate 7b and diol 8, remaining approximately 60% of the unaffected diacetate.  On the other hand, this method represents a route of easy access to 7b, which is almost impossible to obtain by acetylation of the corresponding alcohol, and for obtaining pure enantiomers of 3a.